Research of cervical microbiota alterations with human papillomavirus infection status and women age in Sanmenxia area of China - Hu, Jintao; Wu, Yuhan; Quan, Lili; Yang, Wenjuan; Lang, Jidong; Tian, Geng; Meng, Bo (Frontiers in Microbiology, 2022)
Background Human papillomavirus (HPV) infection is the leading cause of cervical cancer. More and more studies discovered that cervical microbiota (CM) composition correlated with HPV infection and the development of cervical cancer. However, more studies need to be implemented to clarify the complex interaction between microbiota and the mechanism of disease development, especially in a specific area of China. Materials and methods In this study, 16S rDNA sequencing was applied on 276 Thin-prep Cytologic Test (TCT) samples of patients from the Sanmenxia area. Systematical analysis of the microbiota structure, diversity, group, and functional differences between different HPV infection groups and age groups, and co-occurrence relationships of the microbiota was carried out. Results The major microbiota compositions of all patients include Lactobacillus iners, Escherichia coli, Enterococcus faecalis, and Atopobium vaginae at species level, and Staphylococcus, Lactobacillus, Gardnerella, Bosea, Streptococcus, and Sneathia in genus level. Microbiota diversity was found significantly different between HPV-positive (Chao1 index: 98.8869, p < 0.01), unique-268 infected (infections with one of the HPV genotype 52, 56, or 58, 107.3885, p < 0.01), multi-268 infected (infections with two or more of HPV genotype 52, 56, and 58, 97.5337, p = 0.1012), other1 (94.9619, p < 0.05) groups and HPV-negative group (83.5299). Women older than 60 years old have higher microbiota diversity (108.8851, p < 0.01, n = 255) than younger women (87.0171, n = 21). The abundance of Gardnerella and Atopobium vaginae was significantly higher in the HPV-positive group than in the HPV-negative group, while Burkholderiaceae and Mycoplasma were more abundant in the unique-268 group compared to the negative group. Gamma-proteobacteria and Pseudomonas were found more abundant in older than 60 patients than younger groups. Kyoto Encyclopedia of Genes and Genomes (KEGG) and Clusters of Orthologous Groups (COG) analysis revealed the effects on metabolism by microbiota that the metabolism of cells, proteins, and genetic information-related pathways significantly differed between HPV-negative and positive groups. In contrast, lipid metabolism, signal transduction, and cell cycle metabolism pathway significantly differed between multi-268 and negative groups. Conclusion The HPV infection status and age of women were related to CM’s diversity and function pathways. The complex CM co-occurrent relationships and their mechanism in disease development need to be further investigated.